Low-intensity pulsed ultrasound upregulates osteogenesis under inflammatory conditions in periodontal ligament stem cells through unfolded protein response - Han Li (Stem Cell Research & Therapy, 2020)
Abstract Background In periodontal tissue engineering, periodontal ligament stem cells derived from patients with periodontitis (P-PDLSCs) are among the most promising and accessible stem cells for repairing disrupted alveolar bone and other connective tissues around the teeth. However, the inflammatory environment influences the osteogenic differentiation ability of P-PDLSCs. We examined low-intensity pulsed ultrasound (LIPUS) in P-PDLSCs in vitro and in rats with experimental periodontitis to determine whether LIPUS can enhance the osteogenic differentiation of stem cells. Materials and methods P-PDLSCs were harvested and isolated from the periodontal tissues around the teeth of periodontitis patients, and healthy PDLSCs (H-PDLSCs) were obtained from tissues around healthy teeth. After validation by flow cytometry analysis, the P-PDLSCs were cultured in osteogenic medium either pretreated with the endoplasmic reticulum stress (ERS) inhibitor 4-phenyl butyric acid (4-PBA) or not pretreated and then treated with or without LIPUS (90 mW/cm2, 1.5 MHz) for 30 min per day. Cell viability, ERS marker expression, and osteogenic potential were determined between the different treatment groups. LPS-induced H-PDLSCs were used to mimic the inflammatory environment. In addition, we established a model of experimental periodontitis in rats and used LIPUS and 4-PBA as treatment methods. Then, the maxillary bone was collected, and micro-CT and histology staining methods were used to detect the absorption of alveolar bone. Results Our data showed that the P-PDLSCs derived from periodontitis tissues were in a more pronounced ERS state than were the H-PDLSCs, which resulted in the former being associated with increased inflammation and decreased osteogenic ability. LIPUS can alleviate ERS and inflammation while increasing the bone formation capacity of P-PDLSCs in vivo and in vitro. Conclusions LIPUS may be an effective method to enhance the outcome of periodontal tissue engineering treatments of periodontitis by suppressing inflammation and increasing the osteogenic differentiation of P-PDLSCs through the unfolded protein response pathway, and more detailed studies are needed in the future.